New Forms and Tradition in International Cultural Cooperation Between Russia/the USSR and Latin America - N. S. Konstantinova (Ибероамериканские тетради, 2025)
A number of publications by Russian researchers cover the long and eventful history of cultural contacts between Russia and Latin American states. The topic was particularly important in the Soviet period, since at the time foreign cultural policy was one of the mechanisms for maintaining security and the balance of power in a bipolar world. Nowadays the increasing relevance of the issue can be attributed, among other things, to the development of digital technology and the information explosion, whose impact on the cultural ties between Russia and Latin America is to be assessed. In this context, the emphasis is placed on the definition of culture, its essence as a dialogue, as well as the conditions necessary to foster intercultural dialogue, based on UN documents on cultural diversity amid globalization. This paper does not seek to compile all the specific materials on Russia’s cultural ties with Mexico, Brazil and Argentina, three largest countries in the region. However, analyzing not only the concepts behind cultural policies but also how they are implemented is instrumental in exploring the role of culture as the main tool of «soft power». In addition, it is helpful in examining the correlation between tradition and new forms of cultural interaction, which have emerged in response to today’s challenges. The cultural ties between Russia on the one hand and Brazil, Mexico and Argentina on the other are quite representative, hence they can be extrapolated to other countries of Latin America.